Challenges and opportunities in detecting Taenia solium tapeworm carriers in Los Angeles County California, 2009–2014. Issue 4 (December 2015) - Croker, Curtis
Abstract: Carriers of the pork tapeworm, Taenia solium, are the sole source of neurocysticercosis, a parasitic tissue infection that can be chronic and severe. Identifying T. solium tapeworm carriers is challenging. Many are asymptomatic and go undetected and unreported. In addition, T. solium is difficult to distinguish from other Taenia species of less concern. From 2009 to 2014, 24 taeniasis cases were reported to the Los Angeles County (LAC) Department of Public Health. Twenty reports were received solely from our automated electronic laboratory reporting system (ELR), two from health care providers, and two were generated internally from investigation of households with a reported neurocysticercosis case. Further investigation identified one T. solium carrier originally reported by ELR and one identified from a neurocysticercosis case investigation. These results suggest that T. solium tapeworm carriers can be identified from investigation of ELR reports of unspeciated Taenia cases as well as from households of neurocysticercosis cases.